2014
DOI: 10.2134/jeq2012.0422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flue Gas Desulfurization Gypsum Application on Water Quality in a Coastal Plain Soil

Abstract: There are growing concerns regarding the fate of nutrients, especially phosphorus (P), from land application of animal waste. One approach being studied to reduce runoff losses of P is to treat manure or the soil receiving manure with chemical amendments such as gypsum. This study used rainfall simulations to examine the impact of flue gas desulfurization (FGD) gypsum application on runoff nutrient losses on a Coastal Plains soil (Luverne sandy loam; fine, mixed, semiactive, thermic Typic Hapludults). Four rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
(29 reference statements)
4
40
0
Order By: Relevance
“…Increases in maize yields with gypsum rates up to 12.0 Mg ha -1 were reported by Pauletti et al (2014) even under normal precipitation. An increase in nitrogen use efficiency (NUE) associated to gypsum input, as reported by Torbert and Watts (2014) and Caires et al (2015), may be an explanation for the maize yield increase, since a deeper root system provided by soil chemical improvement favors nitrate uptake in subsurface layers, in years with high precipitation. In a meta-analysis, Pittelkow et al (2015) reported that continuous no-tillage management can decrease maize yields up to 7.6 % and in tropical regions this value could be even doubled.…”
Section: Experimental Area Imentioning
confidence: 95%
“…Increases in maize yields with gypsum rates up to 12.0 Mg ha -1 were reported by Pauletti et al (2014) even under normal precipitation. An increase in nitrogen use efficiency (NUE) associated to gypsum input, as reported by Torbert and Watts (2014) and Caires et al (2015), may be an explanation for the maize yield increase, since a deeper root system provided by soil chemical improvement favors nitrate uptake in subsurface layers, in years with high precipitation. In a meta-analysis, Pittelkow et al (2015) reported that continuous no-tillage management can decrease maize yields up to 7.6 % and in tropical regions this value could be even doubled.…”
Section: Experimental Area Imentioning
confidence: 95%
“…At only one of those sites was a further reduction in WSP seen with higher rates of FGD gypsum application. Others have similarly seen beneficial effects of FGD gypsum at low rates (Buckley and Wolkowski, 2014; Torbert and Watts, 2014). At the other three sites with a significant effect, the 1120‐kg ha −1 rate expressed the highest concentration of WSP among the four treatments in collected soil samples.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to use as a fertilizer source or the reclamation of sodic soils (DeSutter and Cihachek, 2009), other uses of FGD gypsum to improve soil health have increased, including use in mitigating subsoil acidity (Shainberg et al, 1989), improving soil physical properties (Norton, 2008; Buckley and Wolkowski, 2014), and reducing runoff losses of P (Torbert and Watts, 2014). In light of these findings, the NRCS now accepts application of gypsum as a Conservation Practice Standard (Code 333) to improve soil health and surface water quality (USDA‐NRCS, 2015).…”
mentioning
confidence: 99%
“…Improved rooting of many crops Farina and Channon, 1988, Sumner M.E., 1993, Alcordo and Rechcigl, 1993Shainberg et a., 1982;Wendell and Ritchey, 1996; 6. Control of soluble phosphorus runoff from fields Norton, 2008;Watts and Torbert, 2009;Bryant et al, 2012;Torbert and Watts, 2014;Endale et al, 2014. been conducted using mined gypsum. Given FGD gypsum's availability and its smaller and more uniform particle size than commercially mined gypsum, this synthetic source may provide greater soil improvement benefits.…”
Section: Objective and Rationale For The Special Collectionmentioning
confidence: 99%
“…One approach being studied to reduce nutrient losses from manure-treated fields is to treat either the manure or soil with chemical amendments such as gypsum. Torbert and Watts (2014) used rainfall simulations to examine the impact of FGD gypsum on runoff nutrient losses from a U.S. Coastal Plains soil (Luverne sandy loam; fine, mixed, semiactive, thermic Typic Hapludults). Four rates of FGD gypsum (0, 2.2, 4.4, and 8.9 Mg ha -1 ) were applied to plots of Coastal bermudagrass (Cynodon dactylon L.) receiving 13.4 Mg ha -1 of poultry litter.…”
Section: Water Qualitymentioning
confidence: 99%